2016
DOI: 10.1213/ane.0000000000001071
|View full text |Cite
|
Sign up to set email alerts
|

2,3-Diphosphoglycerate Concentrations in Autologous Salvaged Versus Stored Red Blood Cells and in Surgical Patients After Transfusion

Abstract: Background Stored red blood cells (RBCs) are deficient in 2,3-diphosphoglycerate (2,3-DPG), but it is unclear how autologous salvaged blood (ASB) compares to stored blood, and how rapidly 2,3-DPG levels return to normal after transfusion. Therefore, we compared levels of 2,3-DPG in stored versus ASB RBCs, and in patients’ blood following transfusion. Methods Twenty-four patients undergoing multilevel spine fusion surgery were enrolled. We measured 2,3-DPG and the oxyhemoglobin dissociation curve (P50) in sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…In contrast, banked blood stored for 25 days had a >90% depletion in 2,3‐DPG, thus shifting the haemoglobin‐oxygen saturation curve substantially to the left, which is associated with decreased oxygen off‐loading and delivery (Fig. ) . Other investigators have shown that salvaged red cells have a twofold or greater amount of 2,3‐DPG relative to banked blood .…”
Section: Red Blood Cell Quality In Salvaged Bloodmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, banked blood stored for 25 days had a >90% depletion in 2,3‐DPG, thus shifting the haemoglobin‐oxygen saturation curve substantially to the left, which is associated with decreased oxygen off‐loading and delivery (Fig. ) . Other investigators have shown that salvaged red cells have a twofold or greater amount of 2,3‐DPG relative to banked blood .…”
Section: Red Blood Cell Quality In Salvaged Bloodmentioning
confidence: 96%
“…For example, 2,3‐DPG, which facilitates offloading of oxygen from the haemoglobin molecule, has been reported to be present in essentially normal levels (<5% depletion) in salvaged blood (Fig. ) . In contrast, banked blood stored for 25 days had a >90% depletion in 2,3‐DPG, thus shifting the haemoglobin‐oxygen saturation curve substantially to the left, which is associated with decreased oxygen off‐loading and delivery (Fig.…”
Section: Red Blood Cell Quality In Salvaged Bloodmentioning
confidence: 98%
“…Amongst other changes,(55) after 7 days of refrigerated storage, the p50 is significantly reduced from a baseline of 27 to 22 then to a nadir of 18 mmHg after 21 days storage. (16) This is echoed in lowered 2,3 DPG levels in patients receiving allogeneic units rather than cell-saver blood during surgery, (56) and in older studies that observed However, the concept of p50 modulation as a transfusion intervention has not been formally tested by any of the aforementioned studies, because "fresh" blood had been stored for an average of 6 ± 5 days (ABLE), 8 ± 5 days (RECESS), or 13 ± 8 days (INFORM), and 2,3 DPG levels would already have been substantially reduced.…”
Section: Red Blood Cell Storage and P50mentioning
confidence: 99%
“…Ex‐vivo rejuvenation of allogeneic RBCs, with a solution containing sodium pyruvate, inosine, adenine and sodium phosphates, increases the levels of ATP and 2,3‐DPG and increases the p50 of stored RBCs by right‐shifting the Oxyhaemoglobin Dissociation Curve towards a state where disassociation of oxygen from haemoglobin is more likely to occur . This is represented by a higher RBC Oxygen Release Capacity (ORC), or the per cent of oxygen removed from haemoglobin across the arterial (100 mmHg O 2 )–venous (40 mmHg O 2 ) pressure gradient .…”
Section: Introductionmentioning
confidence: 99%